2010
DOI: 10.1111/j.1365-2362.2010.02346.x
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine metabolism monitoring: implications in inflammatory bowel diseases

Abstract: Background Thiopurines (TP) are widely used in the management of inflammatory bowel diseases. Side effects and inefficacy are a major concern as they lead to withdrawal of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 79 publications
(98 reference statements)
0
27
0
1
Order By: Relevance
“…These tests were mainly used for evaluating non-responders and suspected non-adherence to therapy, which in fact are the clinical settings where metabolite measurements were deemed useful in the national guidelines [9]. Furthermore, the strongest clinical evidence for metabolite testing is for treatment optimization and for identification of nonresponders that may be in need of alternative medical treatment [23]. Fewer respondents used metabolite measurements for the evaluation of thiopurine-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…These tests were mainly used for evaluating non-responders and suspected non-adherence to therapy, which in fact are the clinical settings where metabolite measurements were deemed useful in the national guidelines [9]. Furthermore, the strongest clinical evidence for metabolite testing is for treatment optimization and for identification of nonresponders that may be in need of alternative medical treatment [23]. Fewer respondents used metabolite measurements for the evaluation of thiopurine-related toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…); (vii) patients with proctitis; and (viii) patients presenting Clostridium diffi cile infection in stool culture. For the 15 patients receiving AZA at inclusion, the rate of 6-thioguanine nucleotide, a marker of treatment effi cacy ( 24 ), was above 250 pmol / 8 × 10 8 erythrocytes.…”
Section: Patient Selectionmentioning
confidence: 97%
“…1), are likely to block the thiopurine pathway, resulting in 6-MeMP overproduction (reviewed in refs. [77][78][79]). Moreover, genome-wide association studies have identified other genetic markers that predict the risk of developing potentially life-threatening, thiopurine-induced pancreatitis in patients with IBD [80].…”
Section: Genotypingmentioning
confidence: 97%